Research on Zigbee Network Temperature Sensor in Intelligent High-Voltage Switch Cabinet - Xin-bo Huang; Yang Zhao; Xiao-hui Zhao; Zhi-jun Liao (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The contacts of high-voltage switchgear will heat and cause safety hazards due to poor contact while running. A Zigbee-based wireless network sensor was designed by the authors of this paper for real-time monitoring of high voltage switchgear when contact temperature rises. This paper first gives a brief introduction to the Zigbee protocol, the protocol stack and the network topology, and then makes an elaboration on the system framework, hardware and software designs of the Zigbee wireless sensor and the design of high-voltage bootstrap power supply. In the end, the field application and analysis proves that based on the Zigbee technology, the online monitoring system of the temperature rise for high-voltage switchgear is stable and capable of real-time reporting the true temperature of the contact. Therefore, the design has the characteristics of high stability, low power consumption, low cost, as well as high flexibility and scalability.